If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+3(-x+38)=102
We move all terms to the left:
2x+3(-x+38)-(102)=0
We add all the numbers together, and all the variables
2x+3(-1x+38)-102=0
We multiply parentheses
2x-3x+114-102=0
We add all the numbers together, and all the variables
-1x+12=0
We move all terms containing x to the left, all other terms to the right
-x=-12
x=-12/-1
x=+12
| 5x^2-26x+14=0 | | x-3/4=2x-1/8 | | 2(x-2)^2=18 | | x-4.5=0 | | 3n-1/3=8/3 | | 7c+9=11c-3 | | z/5-4=31/2 | | 4(x+7)=9x+4 | | 3(x-1)-9=30 | | -4d=2d | | 6x+4x=3476+8x | | 8+4k=8k+7 | | 3(x+8)=13x-16 | | 4x3-32x=0 | | 4^x-2^x=-7 | | -4-8=3n+2 | | 6/4=h/10h= | | 4-n=26 | | 3(b+2)/4=4b-14/8 | | -322=7x-7(-6x+21) | | n+4=26 | | 2x+5=77x-10 | | 25=-5/2x | | 2x-0.9=3x | | 82+p/4=96 | | -14x-7=9x-42 | | 3b+6/4=4b-14/8 | | n-5/5n-10=4/8 | | 27=-9/5x | | 5r-(3r+8)=16 | | 9x+26=12x+20 | | 5d=9d |